2011
DOI: 10.1016/j.taap.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton spectral analysis of benzo[a]pyrene uptake and metabolism in a rat liver cell line

Abstract: Dynamic analysis of the uptake and metabolism of polycyclic aromatic hydrocarbons (PAHs) and their metabolites within live cells in real time has the potential to provide novel insights into genotoxic and non-genotoxic mechanisms of cellular injury caused by PAHs. The present work, combining the use of metabolite spectra generated from metabolite standards using multiphoton spectral analysis and an “advanced unmixing process”, identifies and quantifies the uptake, partitioning, and metabolite formation of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Many of the BaP metabolites and their time-dependent changes in liver cells have been detected in living cells using multiphoton microscopy with the linear unmixing process [13]. Similar time-dependent changes in BaP levels and metabolites in A549 cells are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 67%
“…Many of the BaP metabolites and their time-dependent changes in liver cells have been detected in living cells using multiphoton microscopy with the linear unmixing process [13]. Similar time-dependent changes in BaP levels and metabolites in A549 cells are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 67%
“…However B[ a ]P and its derivatives are photosensitive and are known for their instability in presence of UV light including confocal microscopy. Barhoumi et al . reported on tackling this problem by merging multiphoton spectral analysis and an “advanced un‐mixing process” to detect metabolites of B[ a ]P. The method enabled them to not only detect metabolite formation, but also the uptake and partitioning of B[ a ]P, which could ultimately provide more insights on PAH homeostasis and its mechanisms of action.…”
Section: Polyaromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…The metabolic process of BaP in vertebrates was studied more clearly than that in invertebrates (Barhoumi et al, 2011;Cavalieri and Rogan, 1995;Harris et al, 2009;Jacques et al, 2010;Ramesh et al, 2001). It has been reported that once BaP enters the cells of mammals, it can be oxidated to various BaP epoxides and phenols catalyzed by cytochrome P450 (CYP450).…”
Section: Philippinarummentioning
confidence: 99%
“…Studies on the toxicity of PAHs are focused on several fields such as genotoxicity, hepatotoxicity, developmental toxicity, carcinogenesis and others (Barhoumi et al, 2011;Harris et al, 2009;Jacques et al, 2010;Wang and Jin, 2010), the toxicity effects of PAHs have been detected from a wide range of organisms (Song et al, 2011;Yin et al, 2011;Pan et al, 2008;Wang et al, 2011b;Tuvikene, 1995;Zhang et al, 2009;Kannan and Perrotta, 2008). It is reported that PAHs can cause harmful effects on the skin, body fluids, and the human ability to fight disease after both short-and long-term exposure (U.S. Department of health and human services, 1995).…”
Section: Introductionmentioning
confidence: 99%